Analisis Trend Produksi dan Produktivitas Kelapa Sawit di PT. Perkebunan Nusantara VI Unit Usaha Pangkalan - Khairad, Fastabiqul; Novfirman, Novfirman; Syofiani, Riza; Sari, Dyah Puspita; Sari, Novi Yulanda (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2024)
This research aims to analyze trends in palm oil production and productivity in the PT Perkebunan Nusantara VI Pangkalan Unit. The research method used is quantitative descriptive. The data in this research uses secondary data in the form of time series data for 10 years from 2013 to 2022. Secondary data was obtained directly from PTPN VI Pangkalan Unit. This research uses trend projection analysis with a regression approach. Based on research results, palm oil (FFB) production data for 2013-2022 tends to experience production fluctuations. As predicted for the next 5 years, palm oil production and productivity tends to decline every year. Production and productivity problems which tend to decline at PTPN VI Pangkalan Unit require special attention for improvement in the future.